Efetividade da dança em pacientes com fibromialgia: estudo cego, controlado e randomizado - Baptista, Andréia Salvador [UNIFESP] (2009)
Objective: The aim of the present study was to assess the effectiveness of belly dance as a treatment for pain and improving the quality of life of patients with fibromyalgia. Methods: Eighty female patients with fibromyalgia between 18 to 65 years were randomly allocated to a dance group (n=40) and control group (n=40). Patients in the dance group underwent 16 weeks of belly dance twice a week, while the patients in the control group remained on a waiting list. Patients were evaluated with regard to pain (VAS), function (6MWT), quality of life (FIQ and SF-36), depression (Beck Inventory), anxiety (STAI) and self-image (BDDE) questionnaire. Evaluations were carried out at baseline, 16 weeks and 32 weeks. Results: The dance group achieved significant improvements when compared to the control group in VAS for pain (p<0.001), six-minute walk test (p<0.001), FIQ (p=0.003), BDDE (p<0.009) as well as the pain (p<0.001), emotional aspects (p<0.003) and mental health (p<0.021) domains of the SF-36. Conclusion: Belly dance can be used in the treatment of fibromyalgia to reduce pain and improve function capacity, quality of life and self-image.